2016
DOI: 10.3389/fpls.2016.00876
|View full text |Cite
|
Sign up to set email alerts
|

Plant Growth Promoting Rhizobacteria and Silicon Synergistically Enhance Salinity Tolerance of Mung Bean

Abstract: The present study explored the eco-friendly approach of utilizing plant-growth-promoting rhizobacteria (PGPR) inoculation and foliar application of silicon (Si) to improve the physiology, growth, and yield of mung bean under saline conditions. We isolated 18 promising PGPR from natural saline soil in Saudi Arabia, and screened them for plant-growth-promoting activities. Two effective strains were selected from the screening trial, and were identified as Enterobacter cloacae and Bacillus drentensis using matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
99
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(118 citation statements)
references
References 77 publications
15
99
0
4
Order By: Relevance
“…CS2 inoculation improved quantity of carotenoid, chl 'a', and chl 'b' contents ( Table 2). The increased biomass production in inoculated plants may be credited to increased synthesis of carotenoids along with chl 'a' and chl 'b' [37][38]. Similarly, improved chl contents, growth, and biomass production was observed in inoculated Eruca sativa plants growing under Cd stress [39].…”
Section: Resultsmentioning
confidence: 89%
“…CS2 inoculation improved quantity of carotenoid, chl 'a', and chl 'b' contents ( Table 2). The increased biomass production in inoculated plants may be credited to increased synthesis of carotenoids along with chl 'a' and chl 'b' [37][38]. Similarly, improved chl contents, growth, and biomass production was observed in inoculated Eruca sativa plants growing under Cd stress [39].…”
Section: Resultsmentioning
confidence: 89%
“…; Mahmood et al . ). In this study, EL% was higher in control plants under stress conditions, indicating membrane damages due to osmotic effect.…”
Section: Discussionmentioning
confidence: 97%
“…The great reduction reported in the chlorophyll content in control plants under the salt stress is in line with previous studies (Mahmood et al . ; Panwar et al . ), stating that salinity negatively affects chlorophyll content and membrane stability of leaves.…”
Section: Discussionmentioning
confidence: 99%
“…Under salinity stress, peanut seedlings were able to maintain ion homeostasis, had less ROS buildup with enhanced growth, compared to non-inoculated seedlings (Sharma et al, 2016). Another study by Mahmood et al, (2016) demonstrated that Enterobacter cloacae and Bacillus drentensis acted synergistically with foliar application of silicon to confer salinity tolerance in field-grown Mung beans. Moreover, Brachybacterium saurashtrense strain JG-06, Brevibacterium casei strain JG-08, and…”
Section: Salinitymentioning
confidence: 92%